Optimization of ultrasonication extraction for determination of 16 polycyclic aromatic hydrocarbons in air particle - Thi Duong , Hanh; Trinh, Ha Thu; Thang, Phan Quang; Dung, Nguyen Trung; Dien, Nguyen Tran (Vietnam Journal of Science and Technology, 2018)
The aim of this study is to develop the quick ultrasonication extraction procedure for determination of 16 typical polycyclic aromatic hydrocarbons (PAHs) in air particles. The determination and quantification of PAHs in air particles samples were performed using gas chromatography coupled to mass spectrometry (GC-MS) with the aid of deuterated PAH internal standards. 1ug mixture of PAHs was spiked to a quarter of quartz fiber filter and extracted with four different solvents/solvent mixtures (methanol:dichloromethane, acetone:dichloromethane; acetone:hexane; dichloromethane). Ultrasonication extraction was carried out in dark at uncontrolled and controlled ultrasonication temperature (25-28oC). The unique extraction time (20 minutes) was applied for all experiments. The results showed that high recovery rate of PAHs (82-108%) were obtained with dichloromethane (as extraction solvent) in dark at ultrasonication temperature of 25 to 28oC, while generally low recovery rate of PAHs, especially naphthalene (57%) were obtained with methanol:dichloromethane (1:1). The ultrasonication extraction method with dichloromethane showed good reproductively and repeatability with relative standard deviation of 16 PAHs below 6,14%, confirming that samples analyses were precise. Analytical results of PAHs in air particles collected in Hanoi using the developed ultrasonication extraction procedure showed that 15 out of 16 PAHs were detected, in which high molecular weight (MW) PAHs (>5 rings) were abundance compared to low molecular weight PAHs (< 3 rings). This developed ultrasonication extraction method is quick, easy and sufficient for determination of PAHs in air particle